The Quality Detection Technology and Characterization Marking of Knife Edge. (February 2019) - Su, Zhonghua; Huang, Taizhong; Fan, Lichang; Mi, Haipeng; Deng, Xiong; Deng, Xiaodong
Abstract: The quality and detection of kitchen knives at home and abroad were introduced in this paper. The knife edge toughness index was proposed to measure the comprehensive ability of the blade to resist chipping and curling, and the testing method and testing equipment for the cutter and the chopper were developed. Besides, aiming at the sharpness, durability and toughness which are the key indicators of the knife edge quality, the corresponding detection and identification methods were given.